Faktor-Fator yang Memengaruhi Tingkat Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Badung Utara - Dewi, Gek Ayu Putu Intan Permata; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p18, 2018)
This study consists of 4 independent variables namely the level of understanding of taxpayers, tax sanctions, taxpayer environment, and taxpayer awareness. While the dependent variable is the level of taxpayer compliance. The purpose of the study is to obtain empirical evidence of the influence of the level of understanding of taxpayers, tax penalties, taxpayer environment, and taxpayer awareness at the level of individual taxpayer compliance. The study was conducted at Tax Office Pratama Badung Utara. Samples obtained as many as 100 respondents based on random sampling technique that is taking the respondents randomly.The analysisstechnique is used multiple linearrregression analysis. The resultsoof this study indicateethat the influence of the level of understanding taxpayers haveaaa positive effect on taxpayer complianceelevel. Taxation sanctions, taxpayer environment, and taxpayeraawareness have a negative effect on taxpayer compliance level. Keywords: understanding of taxpayers, taxation sanctions, environmental taxpayers, taxpayer awareness and taxpayer compliance .